Essentials for mutual symmetrical and asymmetrical positions of wrestlers - Fedyaev N.A.; Makarova E.V.; Melentyev A.N.; Tsagolova N.G. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to reveal the differences in symmetrical mutual positions as a method of defense and asymmetrical positions as the method of attack. Besides this, the authors analysed the efficiency of the metod in fighting conditions. Methods and structure of the study. At the purposes of the study video recording and shorthand recording of techniques with different mutual positions of wrestlers had been used. To indicate and measure the reaction forces of the support of wrestlers, the computer complex «AMTI» was used, as well as two dynamometric platforms. The platforms allow measuring the vertical and two horizontal components of the reaction forces of the support. Results and conclusions. Mirror and identical (symmetrical) and asymmetrical mutual arrangements of wrestlers’ body parts relative to the vertical axis during mutual grips were determined. The values ​​of support reaction force (SRF) indicators were determined during symmetrical mutual arrangement of wrestlers and during a bending throw. Thus, during symmetrical mutual arrangements, the SRF indicators were 723,9 N, and during a bending throw – 3317,8 N. Methods for maintaining symmetrical mutual arrangements during defense and their violation during the execution of techniques were tested.